Prevalence of Sexually Transmitted Infections in Premarital Age Adolescents at Siloam Hospital Semarang Period 2019 – 2022 - Olivia Jovina Priyanto; Armita Asri Apsari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Sexually transmitted infection (STI) is an infectious disease that is transmitted through sex. Changing times and views on sexuality are thought to have caused major shifts in sexual habits and lifestyles. Adolescents are uniquely at risk for STIs from a behavioral and biological perspective. Methods: This study is a descriptive study by collecting secondary data in the form of medical records at dermatology and venereology clinics at Siloam Hospital Semarang for the period 2019 - 2022 to see the number of STI cases in premarital adolescents, namely ages ≤24 years in males and ≤20 years in females. Results: The number of STI cases in premarital adolescent boys in 2019 was 28 people (36.4%). In 2020 there were 50 people (25.9%). In 2021 there will be 93 people (29.1%). And in 2022, there will be 112 people (27.7%). Then in premarital adolescent girls, in 2019, there was 1 case of STI (1.3%), 2 people (1%) in 2020, 7 people (2.2%) in 2021, and 8 people (2%) in 2022. Even though the percentage has fluctuated, the number of cases has continued to increase. Conclusion: The number of STI cases in premarital adolescents, age ≤24 years for males and ≤20 years for females, in the 2019 - 2022 period at Siloam Hospital Semarang continues to increase every year. Many factors are thought to influence this phenomenon.